Methods to Monitor and Evaluate the Deterioration of Track and Its Components in a Railway In-Service: A Systemic Review - de Melo, Andre L. O.; Kaewunruen, Sakdirat; Papaelias, Mayorkinos; Bernucci, Liedi L. B.; Motta, Rosangela (Frontiers in Built Environment, 2020)
In planning a new track or improving one in-service, it is fundamental to predict the probable rate of track deterioration as a function of the variables related to the train and its periodicity. A literature investigation has shown there are no track deterioration methods usually available, which can be used as a tool for analysis of track condition of each (re)new railway track. A prediction of them requires accurate quantification of each track component and track geometry behaviours, and a better knowledge of (inter)actions between components and geometry, as well. During an extended survey, more than 100 methods (or studies) related to track deterioration were found, including other literature reviews. Very few of these methods enquiries with several track deterioration issues. This paper aims to build upon with accepted reviews and based on a methodology for systematic critical literature review identifies, evaluates, and classifies the primary studies to predict the track deterioration according to the complexity of both method and validation and study quality. In sequence, it is also assessed whether the technique is established. Afterward, it is identified the gaps and the challenges to be overcome with future researches.